2019
DOI: 10.1136/bmjopen-2019-030670
|View full text |Cite
|
Sign up to set email alerts
|

Empowering healthcare providers through smoking cessation training in Malaysia: a preintervention and postintervention evaluation on the improvement of knowledge, attitude and self-efficacy

Abstract: ObjectivesHealthcare providers are ideally positioned to advise their patients to quit smoking by providing effective smoking cessation intervention. Thus, we evaluate the effectiveness of a 1-day training programme in changing the knowledge, attitude and self-efficacy of healthcare providers in smoking cessation intervention.MethodsA prepost study design was conducted in 2017. The 8-hour Smoking Cessation Organising, Planning and Execution (SCOPE) training comprised lectures, practical sessions and role-play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Our study showed that above average tobacco cessation practice scores was associated with knowledge level, training, organisational support, gender, smoking status and profession as confirmed in the literature. 6 21 35 37 38 Having good knowledge and training were the strongest factors associated positively with tobacco cessation practices among HCW in Qatar. HCW need to be trained for using counselling skills, medication and other tobacco cessation strategies to assist tobacco users quit successfully.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study showed that above average tobacco cessation practice scores was associated with knowledge level, training, organisational support, gender, smoking status and profession as confirmed in the literature. 6 21 35 37 38 Having good knowledge and training were the strongest factors associated positively with tobacco cessation practices among HCW in Qatar. HCW need to be trained for using counselling skills, medication and other tobacco cessation strategies to assist tobacco users quit successfully.…”
Section: Discussionmentioning
confidence: 94%
“…Research indicates that implementation of tobacco cessation intervention is impeded by inadequate training and staff support for HCWs, lack of knowledge about the effects of tobacco on health, and lack of experience in providing counselling and tobacco cessation assistance. 6 7 …”
Section: Introductionmentioning
confidence: 99%
“…The practical session consists of assessment on how to use the tobacco dependence instrument, how to monitor carbon monoxide levels using Smokerlyzer and how to run the quit smoking clinic. The role-play was based on the 5As counselling approach where the participants acted as smoking cessation providers and the facilitator acted as a patient [ 63 ]. Overall, smoking cessation intervention training was an evidence-based strategy to improve healthcare professionals’ self-efficacy and smoking cessation intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study had some limitations that should be addressed. First, the major limitations that this tool has are that this tool is mainly directed toward evaluating training perceptions among healthcare providers (doctors, pharmacists, medical assistants, health education officers, nurses, and others) receiving basic or level I SCOPE training [62]. Second, it relies on self-reported responses from healthcare providers; thus, recall bias, social desirability bias, and information bias should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Here, 403 healthcare providers (e.g., doctors, nurses, pharmacists, medical assistants, and health education officers) completed the paper-and-pencil questionnaire during the face-to-face study. The selected healthcare providers attended a smoking cessation training program called “Smoking Cessation Training Organizing, Planning, and Execution (SCOPE)”, as described in our published paper [62]. The data were collected before the start of the training program.…”
Section: Methodsmentioning
confidence: 99%